Production Performance of Broiler Chickens Using Litter with Different Ratios of Chaff, Sawdust, and Lime - Wa Ode Sitti Nurbaya; Nur Santy Asminaya; Hamdan Has (Pascasarjana Universitas Sulawesi Tenggara, 2023)
This study aims to determine the ratio of rice husk, sawdust, and lime as litter to the production performance of broiler chickens. This research was conducted at the Poultry Farm Unit Laboratory, Faculty of Animal Husbandry, Halu Oleo University. The treatment consisted of: P1 = 100% rice husk, P2 = 100% sawdust, P3 = 70% rice husk + 25% sawdust + 5% lime, P4 = 25% rice husk + 70% sawdust + 5% lime P5 = 47.5% rice husk + 47.5% sawdust + 5% lime. A completely randomized design (CRD) with 5 treatments and 4 replications was used in this study. Each repetition consisted of 5 chickens. Variables observed included ration consumption, body weight gain and feed conversion, litter pH, and temperature. The results showed that broiler chickens' values of feed consumption, body weight gain, and ration conversion were 139.8-145.1 gram/head/day; 71.1-74.6 grams/head/day, and 1.85-2.01. The pH and temperature of the litter ranged between 6.2-8.3 and 33.3-34.2oC. The study concluded that the rice husk, sawdust, and lime ratio had no significant effect (P>0.05) on broiler chickens' consumption, body weight gain, and feed conversion.